Perempuan Desainer Berdikari dalam Industri Kreatif di Indonesia - Agustin, Senja Aprela; Saidi, Acep Iwan; Damajanti, Irma (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
This paper depicts the work of three women designers in the informal sector of the creative industry in Indonesia. The unique works of women designers in designing and building brands of local-domestic products, fashion, decorations, and, accessories produced in home-based studios have made them financially self-sustaining. In addition, this research also shows that the ability of women designers to negotiate in society which still burdens women with domestic activities can be self-supported and develop their businesses. Furthermore, the factors that influence the success of business sustainability include: ’personal style’ design, ability to understand the market, proficiency in computer technology, and the utilization of communication media such as social media and websites. This independent women designer figure in the informal sector indirectly contributes to economic prosperity in Indonesia